PFP: a scalable parallel programming model - Corda, B.C.; Warren, K.H. (Scalable High-Performance Computing Conference (SHPCC-92), 1992)
The Parallel Fortran Preprocessor (PFP) is a programming model for multiple instruction multiple data (MIMD) parallel computers. It provides a simple paradigm consisting of data storage modifiers and parallel execution control statements. The model is lightweight and scalable in nature. The control constructs impose no implicit synchronizations, nor do they require off-processor memory references. The model is portable. It is implemented as a source-to-source translator which requires very little support from the back-end compiler. The implementation has an option to option to produce serial code which can then be compiled for serial execution.< >